Pengunaan Modul dan Media Animasi Dalam Mengurangi Miskonsepsi Siswa Pada Materi Sistem Peredaran Darah di Sman 5 Kota Banda Aceh - Safrida Safrida; Cut Ratna Dewi; Abdullah Abdullah (Majelis Pendidikan Daerah (MPD) Aceh dan Universitas Syiah Kuala, 2017)
This study is designed to determine the effectiveness of the learning module and the animation use in reducing student misconceptions in circulatory system concept in the State Senior High School (SMAN) 5 Banda Aceh. This study was conducted at the SMAN 5 Banda Aceh from November 2015 to May 2016. Out of 105 students of class XI MIA at the SMAN 5 Banda Aceh, 49 students from the class XI MIA3 and class XI MIA4 were selected as the sample of the study. The method used in this study was experimental method, consisting the Pre-test and Post-test Controlled Group Design. The instrument used in this study was the Three Tier diagnostic test that completed with Certainty of Response Index (CRI) method and then the data was analyzed using the independent sample t-test. The study found that that there were significant differences in the learning outcomes between the experimental class and the controlled class with ttabel = 2,02 dan tcount = 4,135 (sig. 0,000 0,05). The students were experienced misconceptions in all of the circulatory system concept. This implied that that the use of the learning module and the animation could reducing student misconceptions in circulatory system concept in the SMAN 5 Banda Aceh